Optimizing Synthetic miRNA Minigene Architecture for Efficient miRNA Hairpin Concatenation and Multi-target Gene Knockdown - Francis Rousset; Patrick Salmon; Simon Bredl; Ophélie Cherpin; Marta Coelho; Renier Myburgh; Marco Alessandrini; Michael Perny; Marta Roccio; Roberto F. Speck; Pascal Senn; Karl Heinz Krause (Elsevier, 2019)
Synthetic microRNA (miRNA) minigenes (SMIGs) have a major potential for molecular therapy; however, their optimal architecture still needs to be determined. We have previously optimized the stem structure of miRNA hairpins for efficient gene knockdown. Here, we investigate the overall architecture of SMIGs driven by polymerase II-dependent promoters. When miRNA hairpins were placed directly behind the promoter, gene knockdown was inefficient as compared with constructs containing an intercalated sequence ("spacer"). Spacer sequence was relevant for knockdown efficiency and concatenation potential: GFP-based sequences (even when truncated or including stop codons) were particularly efficient. In contrast, a spacer of similar length based on a CD4 intronic sequence was entirely inefficient. Spacer sequences influenced miRNA steady-state levels without affecting transcript stability. We demonstrate that with an optimized spacer, up to five concatenated hairpins targeting two different genes are efficiently expressed and able to knock down their respective targets. Transplantation of hematopoietic stem cells containing a CCR5 knockdown SMIG demonstrated a sustained in vivo efficacy of our approach. In summary, we have defined features that optimize SMIG efficiency. Based on these results, optimized knockdown of genes of interest, such as the HIV co-receptor CCR5 and the NADPH oxidase subunit p22phox, was achieved. Keywords: siRNA, miRNA, synthetic miRNA minigene, miRNA hairpins concatenation, multi-target gene knockdown, CCR5, NOX3, hematopoietic stem cells, cochlea, lentivector transduction